Defect Electrocatalysts and Alkaline Electrolyte Membranes in Solid‐State Zinc–Air Batteries: Recent Advances, Challenges, and Future Perspectives. Issue 1 (6th December 2020) - Wu, Mingjie; Zhang, Gaixia; Du, Lei; Yang, Dachi; Yang, Huaming; Sun, Shuhui
Abstract: Rechargeable zinc–air batteries (ZABs) have attracted much attention due to their promising capability for offering high energy density while maintaining a long operational lifetime. One of the biggest challenges in developing all‐solid‐state ZABs is to design suitable bifunctional air‐electrodes, which can efficiently catalyze the key oxygen reduction reaction (ORR)/oxygen evolution reaction (OER) electrochemical processes. The other one is to develop robust electrolyte membranes with high ionic conductivity and superb water retention capability. In this review, an in‐depth discussion of the challenges, mechanisms, and design strategies for the defect electrocatalyst and the electrolyte membrane in all‐solid‐state ZABs will be offered. In particular, the crucial defect engineering strategies to tune the ORR/OER catalysts are summarized, including direct controllable strategies: 1) atomically dispersed metal sites control, 2) vacancy defects control, and 3) lattice‐strain control, and the indirect strategies: 4) crystallographic structure control and 5) metal–carbon support interaction control. Moreover, the most recent progress in designing electrolyte membranes, including polyvinyl alcohol‐based membranes and gel polymer electrolyte membranes, is presented. Finally, the perspectives are proposed for rational design and fabrication of the desired air electrode and electrolyte membrane to improve the performance and prolong the lifetime of all‐solid‐state ZABs. Abstract : Designing suitable bifunctional air‐electrodes and robust electrolyte membranes are the two major challenges in developing all‐solid‐state zinc–air batteries (ZABs). This review provides an in‐depth discussion about recent advances, challenges, mechanisms, and design strategies for defect‐rich electrocatalysts and alkaline electrolyte membranes in all‐solid‐state ZABs. The future perspectives to accelerate the development of all‐solid‐state ZABs are also proposed.